PENGARUH GAYA KEPEMIMPINAN, KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT PLN (PERSERO) UPDK BAKARU - K, Fitriani (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2021)
This study aims to verifythe impact of leadership style, compensation, and work environment on job satisfaction. The research method used is quantitative causal, in line with the research objectives. The study population was 71 people with a sample size of 71 respondents. Research data were collected using a questionnaire. Furthermore, the data were analyzed using multiple linear regression statistical data. The results showed that: 1) leadership style has a positive and significant effect on employee job satisfaction. 2) compensation has a positive and significant impact on employee job satisfaction. 3) the work environment is no significanteffect on employee job satisfaction.